Magnetic Attraction of Gaze: Further Evidence of Hemispheric Imbalance in Schizophrenia? - S. B. Unnithan; A. S. David; J. C. Cutting (Behavioural Neurology)
A case is reported of a young man with a clinical diagnosis of schizophrenia and unusual oculo-motor abnormalities. The relationship between oculo-motor dysfunction and hemispheric balance in schizophrenia is discussed.